CSR in TSL companies - Joanna DYCZKOWSKA (Transport Problems, 2015)
TSL companies are characterized by high dynamics of an increase of incomes, and hence increased shipping. Owing to a rational policy in the area of the consolidation of production and distribution, they may boast of a better use of the means of transport. The purpose of this article is to present the activities in the area of the eco-friendly CSR aspect in the activities of TSL companies taking into consideration particularly logistic operators. The research methods used in the study include an analysis of secondary data, observations and comparative analyses. Road transport in the shipping structure comes first and it constitutes 84% of freights. In the year 2009, in Poland greenhouse gas emissions from road transport amounted to 42.5 million tons (4.84% of the EU member states) and CO emissions were 41.9 million tons (analogically, 4.83% of environment pollutions in the European Union). This causes an emission of fumes into the atmosphere. The policy of sustainable development pursued by logistic operators under corporate social responsibility is a response to the abovementioned data. They take decisions concerning social and environmental aspects. The activities of TSL companies under CSR need to provide an answer to customer expectations and needs, and they have to cause an increase of competitiveness on the market. The selected four largest logistic operators conduct the following eco-friendly activities on the highest level: fume emission reports and the control of these emissions, transport of hazardous goods (ADR), voluntary services in the scope of environmental protection and cooperation with eco-friendly organizations. There are those activities which call for improvement: a limitation of the emission of fumes, waste management and sewage treatment policy.